Becoming a Member of the Russian Nation: The Content of National Identity Underlying the Social Markers of Acceptance for Immigrants in Russia - Dmitry Sergeevich Grigoryev; Albina Alikovna Gallyamova; Elizaveta Shamilevna Komyaginskaya (Peoples' Friendship University of Russia (RUDN University), 2023)
Acculturation expectations of the host society are an integral and important part of the process of mutual acculturation and subsequent adaptation due to intercultural contact. A new approach to acculturation of host society members is examined: the concept of social markers of acceptance, which analyzes socially constructed criteria that indicate immigrants' inclusion in the larger society. The aim of the study was to understand specific social indicators of national identity that Russians consider important for the inclusion of an immigrant into Russian society. The relationship between these markers and a general attitude toward immigrants were investigated, as well as how perceived immigrant status moderates these relationships. A survey with 1,009 participants, the majority of whom identified as ethnic Russian, was conducted. The results indicated that civic indicators of national identity, especially compliance with laws and regulations, were considered the most important and ease of acquiring for immigrants, while ethnic indicators were considered the least important and ease of acquiring. Additionally, socioeconomic and sociocultural indicators were identified as being of intermediate importance and ease of acquiring, which suggested with the concepts of immigrant status and socioeconomic adaptation, along with immigrant intercultural competence and sociocultural adaptation respectively. Finally, the perceived higher status of immigrants was associated with more permeable intergroup boundaries. Research results suggest that the Russian population is inclined toward a civic conceptualization of national identity, preferring a liberal approach to citizenship over a more restrictive one. The study also underscores the influence of perceived immigrant status in shaping the host population's acculturation expectations. As a practical implication of the findings, focusing on social and educational programs that promote legal and civic compliance among immigrants before adopting anti-discrimination measures on the part of the host society is recommend.